2019
DOI: 10.4103/apjon.apjon_10_19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Behavior of University Students toward Human Papillomavirus and Vaccination

Abstract: Objectives: Human papillomavirus (HPV) causes cervical cancer. This study aimed to determine the knowledge and attitude of university students toward HPV infection and vaccine prevention in Turkey. Methods: A total of 1563 female and male university students participated in the study. The study design was descriptive and cross-sectional. The study included students enrolled in the departments of faculties and vocational schools. Results: In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 33 publications
4
22
1
2
Order By: Relevance
“…Knowledge gaps between males and females about HPV and its vaccine has been found in both medical students [18][19][20][21] and in the non-university population, corroborating our data [22,23]. While the higher level of knowledge found in females in this study is a function of the personal and individual experiences, since medical students of both sexes are exposed to the same amount of theoretical concepts before graduation [3]. In addition, a study shows that male parents underestimate the effects of HPV in males and prioritize the vaccine for women PLOS ONE [24].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Knowledge gaps between males and females about HPV and its vaccine has been found in both medical students [18][19][20][21] and in the non-university population, corroborating our data [22,23]. While the higher level of knowledge found in females in this study is a function of the personal and individual experiences, since medical students of both sexes are exposed to the same amount of theoretical concepts before graduation [3]. In addition, a study shows that male parents underestimate the effects of HPV in males and prioritize the vaccine for women PLOS ONE [24].…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have found low HPV vaccination rates among medical students was related to lack of knowledge about vaccine safety and efficacy, religious and cultural issues, and lack of government programs that cover the age range of students [28][29][30][31]. In addition, vaccination rates are higher in countries with national HPV vaccination programs [3]. Vaccinated students have been found to be more willing to recommend HPV vaccination and clarify patient questions and are more likely to follow the recommendations and take every opportunity to offer HPV vaccine [30,31].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study conducted by Cinar et al . on the level of knowledge about HPV among non‐medical university students, 79% of the students expressed that they could not share sexual matters with their family . In another study done by Arslan et al ., only 22.5% of university students were found to have acquired their knowledge on sexually transmitted diseases from their parents .…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] More female university students stated that they also heard of HPV and HPV vaccination in a study conducted in Turkey. [ 27 ] Females care more about the disease of themselves, and this could explain the different results between male and female participants. More participants from the city than from rural areas knew that “Cervical cancer screening can prevent morbidity and mortality from cervical cancer.” Similar differences between those in the city and rural areas also were found in other studies.…”
Section: Discussionmentioning
confidence: 99%